Metode Tahlili dan Aplikasinya dalam Penafsiran Al-Quran - Miftahurrahmat Miftahurrahmat; Syabuddin Syabuddin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The tahlili method is one of the important approaches in Qur'anic interpretation that emphasizes a very intensive analysis of the holy verses of the Qur'an. This study aims to explore the characteristics, advantages, and disadvantages of the tahlili method and its application in the context of Qur'anic interpretation. By using a qualitative approach and library research, data is collected through a review of relevant literature, both from printed and electronic sources. The results show that the tahlili method, which was first applied in the third period after Tabi'in, has the ability to convey the messages of the Qur'an in a concise and global manner, so that it is easily understood by Muslims. This method also has systematic steps, which include describing the verses of the Qur'an and explaining the meaning of vocabulary according to the rules of Arabic, including general analysis and selection of diction that reflects the Qur'anic lafaz. Although this method has advantages in terms of clarity and freedom from the influence of interpretation, there are also weaknesses that need to be considered, such as parcial instructions and the potential for ineffective interpretation. The author hopes that this research can help contribute to the understanding of the tahlili method and improve a more effective and applicable way of interpreting the Qur'an.